Low-Power Low-Voltage Sigma-Delta Modulators in Nanometer CMOS - Yao, Libin; Steyaert, Michiel; Sansen, Willy; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2006)
Low-Power Low-Voltage Sigma-Delta Modulators in Nanometer CMOS addresses the low-power low-voltage Sigma-Delta ADC design in nanometer CMOS technologies at both the circuit-level and the system level. The low-power low-voltage Sigma-Delta modulator design at the circuit level is introduced. A design example is presented in this book. This design is the first published Sigma-Delta design in a 90-nm CMOS technology and reaches a very high figure-of-merit. At the system level, a novel systematic study on the full feedforward Sigma-Delta topology is presented in this book. As a design example, a fourth-order single-loop full feedforward Sigma-Delta modulator design in a 130-nm pure digital CMOS technology is presented. This design is the first design using the full feedforward Sigma-Delta topology and reaches the highest conversion speed among all the 1-V Sigma-Delta modulators to date.
ADCs in Nanometer CMOS Technologies -- Principle of ?-? ADC -- Low-Power Low-Voltage ?-? ADC Design in Nanometer CMOS: Circuit Level Approach -- Low-Power Low-Voltage ?-? ADC Design in Nanometer CMOS: System Level Approach -- Conclusions.
Keywords: ENGINEERING; ENGINEERING DESIGN; ELECTRONICS; TELECOMMUNICATION; SYSTEMS ENGINEERING; NANOTECHNOLOGY; ENGINEERING; CIRCUITS AND SYSTEMS; ELECTRONICS AND MICROELECTRONICS, INSTRUMENTATION; COMMUNICATIONS ENGINEERING, NETWORKS; ENGINEERING DESIGN; ELECTRONIC AND COMPUTER ENGINEERING; NANOTECHNOLOGY